The Disability Rights Movement: From Charity to Confrontation - Fleischer, Doris Zames; Zames, Frieda (Temple University Press, 2011)
In this updated edition, Doris Zames Fleischer and Frieda Zames expand their encyclopedic history of the struggle for disability rights in the United States, to include the past ten years of disability rights activism.The book includes a new chapter on the evolving impact of the Americans with Disabilities Act, the continuing struggle for cross-disability civil and human rights, and the changing perceptions of disability. The authors provide a probing analysis of such topics as deinstitutionalization, housing, health care, assisted suicide, employment, education, new technologies, disabled veterans, and disability culture. Based on interviews with over one hundred activists,The Disability Rights Movementtells a complex and compelling story of an ongoing movement that seeks to create an equitable and diverse society, inclusive of people with disabilities.